2022
DOI: 10.3390/antibiotics11010103
|View full text |Cite
|
Sign up to set email alerts
|

Methicillin-Resistant Staphylococcus aureus from Peninsular Malaysian Animal Handlers: Molecular Profile, Antimicrobial Resistance, Immune Evasion Cluster and Genotypic Categorization

Abstract: Staphylococcus aureus (S. aureus) infections, particularly methicillin-resistant Staphylococcus aureus (MRSA) in humans and animals, have become a significant concern globally. The present study aimed to determine the prevalence and antibiogram of S. aureus isolated from animal handlers in Peninsular Malaysia. Furthermore, the genotypic characteristics of S. aureus isolates were also investigated. Nasal and oral swab samples were collected from 423 animal handlers in Peninsular Malaysia. The antibiogram profil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…As a result, it seems possible that MRSA could spread within poultry farms as well as through the air. In addition, it was discovered that animal handlers who had frequent contact with both pets and animals were more likely to have MRSA in their bodies than the animals they were caring for [28]. Thus, healthy rabbits in this study possibly derived MRSA from their environment as well as from their owner.…”
Section: Discussionmentioning
confidence: 78%
“…As a result, it seems possible that MRSA could spread within poultry farms as well as through the air. In addition, it was discovered that animal handlers who had frequent contact with both pets and animals were more likely to have MRSA in their bodies than the animals they were caring for [28]. Thus, healthy rabbits in this study possibly derived MRSA from their environment as well as from their owner.…”
Section: Discussionmentioning
confidence: 78%
“…The MRSA isolates demonstrated resistance to multiple classes of antibiotics commonly used for treating MRSA infections ( Chai et al, 2022 ). The risk ratio associated with MRSA isolated from cancer patients revealed a resistance pattern to erythromycin, ciprofloxacin, fusidic acid, co-trimoxazole, tetracycline, gentamicin, and clindamycin.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies from the Netherlands reported the highest prevalence of IEC type B variants among isolates ( van Wamel et al, 2006 , Verkaik et al, 2011 ), as type B is the predominant variant in human infectious isolates. Notably, a greater prevalence of Type E IEC variants has been documented in MRSA strains from Malaysia ( Chai et al, 2022 ). Our study identified 6 % Type E and 15 % Type B IEC variants among all isolates.…”
Section: Discussionmentioning
confidence: 99%
“…Antimicrobial resistance (AMR) in bacteria is a natural phenomenon [10], considered to be a significant health threat, and the emergence of antibiotic-resistant bacteria needs up-to-date treatment protocols [11,12]. According to a reported economic study, the number of fatalities associated with antibiotic-resistant microbes will increase exponentially from 700,000 per year in 2015 to 10 million per year in 2050 [13].…”
Section: Introductionmentioning
confidence: 99%